Adopting International Financial Reporting Standard No. (9) Financial Instruments - Recognition and Measurement of Accounting for Shares and its Reflection on the Financial Statements of Companies (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Many financial institutions invest their surplus funds in stocks, either to obtain dividends or for trading purposes and to obtain profits from the difference between the cost and the selling price, and investment in shares represents an important part of the financial position of financial institutions applying to the common accounting system of banks and insurance companies, in addition to their impact It is clear on the result of the activity of these institutions.The aim of the research is to define what the shares and their types are, and to indicate the accounting treatments needed to move towards the process of adopting the International Financial Reporting Standard No. (9) and its reflection on its financial statements. Its activity and the researchers recommended the need to adopt the International Financial Reporting Standard No. (9) to hold companies accountable, especially that their current book values ​​ Do not reflect current market indicators.